The Effects of Long-term Storage on Commonly Measured Serum Analyte Levels. Issue 3 (May 2018) - Kleeberger, Cynthia; Shore, David; Gunter, Elaine; Sandler, Dale P.; Weinberg, Clarice R.
Abstract : Background: Cohort studies typically bank biospecimens for many years before assay and investigators do not know whether levels of analytes have degraded. Methods: We collected control samples from 22 nonstudy participants using the same enrollment criteria and specimen collection, processing, and storage protocols as The Sister Study. Serum samples were assayed for 21 analytes at collection and 6 years later. For each sample, the difference between the result at baseline and at 6 years was calculated for each analyte. Results: Some of the analytes experienced a marked decrease in concentration after 6 years of frozen storage in liquid nitrogen vapor, compared with their baseline value. The confidence interval for the mean paired difference excluded 0 for 8 of the 21 analytes tested (aspartate transaminase, total cholesterol, estradiol, glucose, high-density lipoprotein [HDL] cholesterol, luteinizing hormone, protein, and triglycerides). Two analytes, lactate dehydrogenase and sex hormone binding globulin, increased substantially in concentration over time (confidence interval excluded 0). For compounds substantially affected by storage time, the internal laboratory control variance was greater than the estimated mean percent change for HDL cholesterol and luteinizing hormone, indicating that extent of degradation for these analytes did not exceed technical variation. Conclusions: Despite evidence for systematic changes over long-term storage, correlations between baseline and later measures were high with little relation between size of the correlation and estimated mean difference across time points. QC experiments to assess the impact of long-term storage on anticipated analytes of interest are important in planning cohort studies with banked samples. Abstract : Supplemental Digital Content is available in the text.